2008
DOI: 10.1210/me.2007-0128
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Aryl Hydrocarbon Receptor Nuclear Translocator Functions as an Estrogen Receptor β-Selective Coactivator, and Its Recruitment to Alternative Pathways Mediates Antiestrogenic Effects of Dioxin

Abstract: The biological effects of dioxins are mediated by the aryl hydrocarbon receptor (AhR) and its dimerization partner, the AhR nuclear translocator (ARNT), and include interference with hormonal signaling pathways like the response to estrogens. The effects of estrogens are mediated by two estrogen receptor (ER) isoforms, ERalpha and ERbeta, which belong to the family of nuclear receptors. We have previously shown that ARNT can act as coactivator of the ERs. In this study, we show that recruitment of ARNT to AhR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 50 publications
3
82
1
1
Order By: Relevance
“…In 1962, with the use of high specific activity tritiated 17β-estradiol, Elwood V. Jensen's group provided the first firm evidence regarding the existence of recep-and O 'Malley, 2000;Lonard and O'Malley, 2006), including responses to endocrine disrupters (Safe et al, 2002;Shanle and xu, 2011). these features may be altered either directly or indirectly by endocrine disrupters, which can induce cellular responses by binding to other receptor components acting as transcription factors, such as the aryl hydrocarbon receptor, leading to cross-talk between distinct signaling pathways (Safe and Wormke, 2003;Rüegg et al, 2008). endocrine disruption would then result from the combined action of a non-physiologic set of proteins synthesized following the expression of a perturbed mRNA pool in affected cells (Fig.…”
Section: Cell-based Assays For Toxicity Testingmentioning
confidence: 99%
“…In 1962, with the use of high specific activity tritiated 17β-estradiol, Elwood V. Jensen's group provided the first firm evidence regarding the existence of recep-and O 'Malley, 2000;Lonard and O'Malley, 2006), including responses to endocrine disrupters (Safe et al, 2002;Shanle and xu, 2011). these features may be altered either directly or indirectly by endocrine disrupters, which can induce cellular responses by binding to other receptor components acting as transcription factors, such as the aryl hydrocarbon receptor, leading to cross-talk between distinct signaling pathways (Safe and Wormke, 2003;Rüegg et al, 2008). endocrine disruption would then result from the combined action of a non-physiologic set of proteins synthesized following the expression of a perturbed mRNA pool in affected cells (Fig.…”
Section: Cell-based Assays For Toxicity Testingmentioning
confidence: 99%
“…In fact, competition between ER and AhR for ARNT has been shown to be at least partly responsible for the anti-estrogenic properties of the dioxin TCDD (Brunnberg et al 2003, Rüegg et al 2007). Although ARNT is not considered to be a classical transcriptional co-activator, it shares many properties with the SRC family of co-activators and has been shown to act as co-activator of the ERs (Brunnberg et al 2003), in particular of ERb (Rü egg et al 2007). Competition for common co-activators occurs also within the NR family; it has been shown that activation of CAR, a NR involved in metabolism of xenobiotic substances, inhibits ER activity by reducing the available levels of the p160 co-activator GRIP-1 (Min et al 2002).…”
Section: Interference With Co-activator Recruitmentmentioning
confidence: 99%
“…In this regard, ARNT is said to function as a coactivator for ER, but with selectivity for ER␤. Thus, ARNT recruitment to AhR target genes can reduce the transcription of ER target genes (Rü egg et al, 2008). Concerning proestrogenic effects, Ohtake et al (2003) reported that AhR ligand treatment can induce ER-mediated transcription through the formation of an AhR ⅐ ARNT ⅐ ER complex (Brosens and Parker, 2003).…”
Section: Downloaded Frommentioning
confidence: 99%